THE IMPORTANCE OF TEACHER – STUDENTS INTERACTION IN COMMUNICATIVE LANGUAGE TEACHING (CLT) - Mohammad Abraham Akbar Eisenring; Margana Margana (PRASASTI: Journal of Linguistics, 2019)
Interaction takes crucial part in English language teaching and learning. It could determine the successfulness of teaching and learning in the classroom. Relying on the fact, interaction becomes the main means for teacher and students to exchange their ideas, feelings, opinions, insights, and etc. Especially for the teachers themselves, maintaining interaction with students is considered to be very important thing. In this case, teachers need to employ some proper strategies and approaches in order to deal with such kind of activity. Nowadays, a great number of teachers apply student-centered approach more than teacher-centered one in the way they teach English. Student-centered approach is believed to be able to encourage the teachers to raise their awareness to interact more with the students by implementing Communicative Language Teaching (CLT). In this library-based research paper, the writers would like to elevate the importance of classroom interaction in Communicative Language Teaching (CLT) as an important means for teachers in their respective classrooms.